The Significance of Professor Elena Rossinskaya’s Scientific School of Forensic Expertology for the Development of Forensic Science (in Celebration of the Scientist’s Milestone Birthday) - E. I. Galyashina (Теория и практика судебной экспертизы)
The article is devoted to the contribution review of forensic expertology scientific school created at the Department of Forensic Expertise of Kutafin Moscow State Law University (MSAL) under the leadership of professor E.R. Rossinskaya to the improvement of quality and efficiency of forensic activities. A brief biographical note is given which reflects the main milestones of the formation of the famous scientist and teacher, leader of the national forensic science and forensic expertise. The author concludes that the national scientific school of forensic expertology has received international recognition and world sounding largely due to the personal qualities of its leader – professor E.R. Rossinskaya, who is celebrating her milestone birthday this year.